The Concept of Islamic Modernism in Indonesia According to Hamka (Hamka's Study of Modern Sufism) - Muhammad Rizqy Nawwari (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
Sufism has an important role in the spread of Islam in Indonesia. Islamization in Indonesia is colored by the practice of Sufism spread in various tariqa groups which are still preserved. In its development, Sufism began to shift, until it approached the circumstance, and moved away from the origin of Sufism until many Islamic modernists in the world rejected the teachings of Sufism. Hamka as an Islamic thinker in Indonesia expresses the concept of modern Sufism that restores it to its purity according to the spirit in Islam. Hamka's modern Sufism concept became a new perspective on Islamic Modernism, especially in Indonesia.